The nanostructure's management is the basis for a functional fatty foods' production - Ivanov, Sergey; Rashevska, Tamara (My University, 2011)
For the first time the functional types of butter with herbal supplements (HS) are developed. The effect of HS on micro-and nanostructure of developed types of butter was studied. Based on the results of the study it was recommended to use HS to control the formation of the butter's nanostructure and its quality, physical and chemical properties.
Наноструктурне управління є основою для виробництва функціональних жирових продуктів
Keywords: вершкове масло збагачене; butter; кріопорошок; cryopowder; кафедра технології молока і молочних продуктів; кафедра експертизи харчових продуктів